Coal-based solid waste large-scale green resource utilization method
Patent Information
- Application Number
- CN202611181234.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-09-29
AI Technical Summary
[0005]鉴于上述分析,本发明旨在提供一种煤基固废资源化利用方法,用以解决现有技术中赤泥制备固化建筑材料强度低以及重金属浸出、赤泥处理废水吸附容量低以及结构性能不足、改性赤泥吸附剂制备工艺复杂、原料团聚难以分散导致资源化利用率低中的至少一个问题
A)本发明提供的煤基固废资源化利用方法,采用干态粉体赤泥(掺量40~50%),使得产品能够替代C50及以上等级水泥混凝土应用于道路基层、隧道回填等承重工程,工艺简单、成本低廉,为赤泥的大规模绿色资源化利用提供了兼具力学性能、环境安全性和经济可行性的方案。
Smart Images

Figure CN122831622A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization technology, and particularly relates to a method for the resource utilization of coal-based solid waste. Background Technology
[0002] Currently, the resource utilization of red mud mainly focuses on three major technological directions, but all of them have significant drawbacks: Firstly, while adding cement, lime, and other cementing components to activate red mud to prepare solidified building materials is feasible, the low activity of red mud itself means that even with high admixtures (≥40%), the 28-day compressive strength of the material is often below 30 MPa, failing to meet engineering requirements. Furthermore, alkali activation technology to enhance activity requires the addition of costly activators such as NaOH and water glass, and the risk of heavy metal leaching during long-term service remains unresolved. Additionally, Cu²⁺ leaching in acidic environments is a significant concern. + Cd² + The leaching concentration is prone to exceed the standard.
[0003] Secondly, the adsorption properties of red mud's own iron and aluminum oxides can be used to treat wastewater. However, the adsorption capacity of red mud is limited when used directly as an adsorbent. Although composite modification (such as doping with bentonite and activated carbon) can improve the adsorption rate, high dosage of additives will lead to material strength deterioration and reduced durability, and cannot take into account both adsorption function and structural performance.
[0004] Thirdly, although the use of novel adsorbents such as magnetic nanomaterials can achieve a high Cr(VI) adsorption capacity, the preparation process of such adsorbents is complex, the raw material cost is high, and large-scale production is difficult, making it difficult to apply to engineering practice. Summary of the Invention
[0005] In view of the above analysis, the present invention aims to provide a method for the resource utilization of coal-based solid waste, in order to solve at least one of the following problems in the prior art: low strength of solidified building materials prepared from red mud and heavy metal leaching; low adsorption capacity and insufficient structural performance of wastewater treated with red mud; complex preparation process of modified red mud adsorbent; and low resource utilization rate due to the difficulty in dispersing raw material agglomeration.
[0006] The objective of this invention is mainly achieved through the following technical solutions: This invention provides a method for the resource utilization of coal-based solid waste, comprising the following steps: Step 1: Pre-treat the diatomaceous earth to obtain pre-treated diatomaceous earth; Step 2: Weigh the raw materials and mix them evenly to obtain a mixture; Step 3: Add water to the mixture and stir, with a water-to-binder ratio of 0.35~0.5, to form a uniform slurry; Step 4: Pour the uniform slurry into the mold and vibrate it to compact it, so as to obtain the molded diatomaceous earth modified red mud-based cementitious material; The raw materials include a dry mixture and an activator. The dry mixture consists of red mud (40-50%), silicate cement (20-40%), and granulated blast furnace slag (20-30%) by mass fraction. The activator consists of pretreated diatomaceous earth (10-15%), calcium chloride (1-3%), and water-reducing agent (0.2-0.3%) by percentage of the total mass of the dry mixture.
[0007] Furthermore, the pretreatment in step 1 is an acid washing pretreatment.
[0008] Furthermore, in step 1, the pickling pretreatment includes the following steps: Diatomaceous earth raw material is mixed with 30% dilute sulfuric acid at a solid-liquid ratio of 1~2:5 g / mL, stirred at 20~30℃ for 24~36h, vacuum filtered, washed with deionized water until the pH of the filtrate is 7, and dried at 100~105℃ to constant weight to obtain pretreated diatomaceous earth.
[0009] Furthermore, the pretreatment in step 1 is a calcination pretreatment.
[0010] Furthermore, in step 1, the calcination pretreatment includes the following steps: The diatomaceous earth raw material is heated to 450-480℃ at a heating rate of 5-8℃ / min, calcined at a constant temperature for 150-180min, and then naturally cooled to obtain pretreated diatomaceous earth.
[0011] Furthermore, step 5 is followed by the following steps: Curing of the formed diatomaceous earth modified red mud-based cementitious material.
[0012] Furthermore, the maintenance in step 1 includes the following steps: After the molded diatomaceous earth-modified red mud-based cementitious material is cured at a temperature of 18~22℃ and a relative humidity of ≥95% for 24~36 hours, it is demolded and then cured for a longer period.
[0013] Furthermore, step 2 includes the following steps: Step 2a: Dry mix red mud, silicate cement, and granulated blast furnace slag at 300~350 r / min for 2~5 min; Step 2b: Dissolve calcium chloride and water-reducing agent in a portion of water beforehand, and stir until completely dissolved; Step 2c: First, add the activator solution to the solution obtained in step 2b and stir slowly once, then add the pretreated diatomaceous earth and stir slowly a second time; finally, add the remaining water and stir quickly.
[0014] Furthermore, the stirring speed for the first and second slow stirring is 200~220 r / min, and the stirring time is 2~4 min.
[0015] Furthermore, the speed of rapid stirring is 600~620 r / min, and the stirring time is 3~4 min.
[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: A) The coal-based solid waste resource utilization method provided by this invention uses dry powdered red mud (admixture amount 40~50%), which enables the product to replace C50 and above grade cement concrete in load-bearing projects such as road base and tunnel backfill. The process is simple and the cost is low, providing a solution for the large-scale green resource utilization of red mud that combines mechanical performance, environmental safety and economic feasibility.
[0017] B) The coal-based solid waste resource utilization method provided by this invention, through the synergistic effect of hydration enhancement of cementitious materials and physical / chemical adsorption of diatomaceous earth, can comprehensively achieve high-strength structural performance and long-term solidification of heavy metals in red mud-based cementitious materials. Pretreated diatomaceous earth (5%~15%) is used as the core functional adsorption-enhancing component, utilizing its high specific surface area (≥2.05m²). 2 The porous structure ( / g) constructs a dual barrier of chemical fixation of hydration products and physical interception of diatomite in the cement-slag-red mud ternary cementitious system.
[0018] C) The coal-based solid waste resource utilization method provided by this invention does not use the strong alkaline activators such as high dosage of NaOH and water glass in the existing technology. Instead, it adopts a low dosage of calcium chloride (1%~3%) for mild activation and a low water-cement ratio (0.35~0.5) for densification design. While ensuring the fluidity of the slurry, it controls the pH of the leachate at ≤12.15 (non-corrosive), thereby mitigating the risks of efflorescence, alkali-aggregate reaction and heavy metal re-dissolution in acidic environments during long-term service of high-alkali systems.
[0019] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0020] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0021] Figure 1 The flowchart illustrates the coal-based solid waste resource utilization method provided by this invention. Detailed Implementation
[0022] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0023] This invention provides a method for the resource utilization of coal-based solid waste, see [link to relevant documentation]. Figure 1 This includes the following steps: Step 1: Pre-treat the diatomaceous earth (e.g., acid washing or calcination) to obtain pre-treated diatomaceous earth; Step 2: Weigh the raw materials and mix them evenly to obtain a mixture; Step 3: Add water to the mixture and stir. The water-to-binder ratio is 0.35~0.5 to form a uniform slurry. Step 4: Pour the uniform slurry into the mold, vibrate to compact it, and scrape the surface smooth to obtain the shaped diatomaceous earth modified red mud-based cementitious material.
[0024] The raw materials include a dry mixture and an activator. The dry mixture consists of 40-50 parts red mud, 20-40 parts silicate cement and 20-30 parts granulated blast furnace slag by mass fraction. The activator consists of 10-15 parts pretreated diatomaceous earth, 1-3 parts calcium chloride and 0.2-0.3 parts water-reducing agent by percentage of the total mass of the dry mixture.
[0025] For example, the strength grade of silicate cement is P•O42.5R, the grade of granulated blast furnace slag is S95, the particle size of diatomaceous earth raw material is 800 mesh, the main component is SiO2≥85%, and the water-reducing agent is a polycarboxylate-based water-reducing agent with a water reduction rate≥25%.
[0026] Compared with existing technologies, the coal-based solid waste resource utilization method provided by this invention uses dry powdered red mud (with a dosage of 40-50%), enabling the product to replace C50 and above grade cement concrete in load-bearing projects such as road base and tunnel backfill. The process is simple and low-cost, providing a solution for the large-scale green resource utilization of red mud that combines mechanical performance, environmental safety and economic feasibility.
[0027] Simultaneously, through the synergistic effect of hydration enhancement of cementitious materials and the physical / chemical adsorption of diatomaceous earth, high-strength structural performance and long-term solidification of heavy metals can be comprehensively achieved in red mud-based cementitious materials. Pretreated diatomaceous earth (5%~15%) is used as the core functional adsorption-enhancing component, utilizing its high specific surface area (≥2.05m²). 2 The porous structure ( / g) constructs a dual barrier of chemical fixation of hydration products and physical interception of diatomite in the cement-slag-red mud ternary cementitious system.
[0028] It should be noted that this invention does not use strong alkaline activators such as high dosage of NaOH and water glass as in existing technologies. Instead, it adopts a low dosage of calcium chloride (1%~3%) for mild activation and a low water-cement ratio (0.35~0.5) for densification. While ensuring the fluidity of the slurry, the pH of the leachate is controlled at ≤12.15 (non-corrosive), thereby mitigating the risks of efflorescence, alkali-aggregate reaction, and heavy metal re-dissolution in acidic environments during long-term service of high-alkali systems.
[0029] Specifically, the roles of each component in the above-mentioned dry powder mixture and the interactions between the components are as follows: The Ca(OH)2 generated during the hydration of silicate cement (20-40%) provides an alkaline environment, while the Ca released from the dissociation of calcium chloride (1-3%)... 2+ and Cl - Exhibits dual catalytic effects: Ca 2+ It promotes the breaking of Si-O and Al-O bonds in the glassy network structure of slag, accelerating the reaction of pozzolanic materials to generate additional CSH gel; Cl - This accelerates the hydration rate of C3S and C2S in cement clinker, causing the early hydration heat release peak to occur earlier.
[0030] Granulated blast furnace slag (20%~30%) not only participates in the above reactions as an auxiliary cementitious component, but its high specific surface area can also fill the micropores between red mud particles and cement hydration products as an active micro-aggregate, and the porosity of the matrix is significantly reduced through particle size distribution optimization.
[0031] The active Al2O3 and SiO2 in red mud (40%~50%) undergo ion exchange reactions with CSH gel generated during cement hydration under the combined activation of Ca(OH)2 and CaCl2. 2+ Replace Na on the surface of red mud particles + This promotes the formation of low-alkalinity hydrated calcium silicate, further densifying the interface transition zone.
[0032] The introduction of pretreated diatomaceous earth (5%~15%) and its multi-level interaction with the cementing system. On the one hand, after pretreatment, the specific surface area of the diatomaceous earth is ≥2.05~2.51m². 2 / g, pore volume ≥0.012~0.018cm³ 3 / g, its abundant silanol groups (Si-OH) on the surface are deprotonated to Si-O in alkaline slurry. - This forms negatively charged adsorption sites for heavy metal cations (Cd). 2 + Pb 2+On the one hand, it exhibits strong electrostatic adsorption and surface complexation; on the other hand, its mesoporous structure captures heavy metal ions and complexes migrating during hydration through physical interception; furthermore, diatomaceous earth deeply participates in the hydration reaction at the chemical level: its highly active amorphous SiO2... 2 Silicate ions (SiO3) dissolve in an alkaline environment. 2- ), and free Ca in the slurry 2+ It reacts with heavy metal ions to form CSH gel and heavy metal silicate precipitates, providing additional amorphous nucleation sites for CSH gel and promoting the orderly growth and structural densification of hydration products.
[0033] Furthermore, in order to address the issue of incomplete hydration, the following steps are included after step 5: Curing of the formed diatomaceous earth modified red mud-based cementitious material.
[0034] Specifically, maintenance includes the following steps: After the molded diatomaceous earth-modified red mud-based cementitious material is cured at a temperature of 18~22℃ and a relative humidity of ≥95% for 24~36 hours, it is demolded and then cured for a longer period.
[0035] By adopting the above-mentioned curing method, the cementitious system can be guaranteed to fully complete the hydration reaction, so that the hydration products inside the material grow uniformly, the pore structure is further optimized, and finally the mechanical strength and heavy metal curing effect that meet the design requirements can be stably obtained.
[0036] To address the issue of insufficient pretreatment effectiveness, the above-mentioned pickling pretreatment, for example, includes the following steps: Diatomaceous earth raw material was mixed with 30% dilute sulfuric acid at a solid-liquid ratio of 1-2:5 g / mL, stirred at 20-30℃ for 24-36 h, vacuum filtered, and washed with deionized water until the filtrate pH=7. The mixture was then dried at 100-105℃ to constant weight to obtain pretreated diatomaceous earth. After acid washing, the specific surface area of the diatomaceous earth was ≥2.05 m² / g. 2 / g, pore volume ≥0.012cm³ 3 / g, with an As adsorption rate ≥66.9%.
[0037] Accordingly, the above-mentioned calcination pretreatment includes the following steps: Diatomaceous earth raw material is heated to 450-480℃ at a heating rate of 5-8℃ / min, calcined at a constant temperature for 150-180min, and then naturally cooled to obtain pretreated diatomaceous earth. After calcination, the diatomaceous earth has a specific surface area ≥2.51m². 2 / g, pore volume ≥0.018cm³ 3 / g, with an adsorption rate of ≥75.0% for Cd.
[0038] In order to solve the problem of raw material agglomeration and difficulty in dispersion, step 2 above includes the following steps: Step 2a: Add red mud, silicate cement, and granulated blast furnace slag to a mixer and dry mix at 300~350 r / min for 2~5 min to make the three major cementitious components initially uniform and reduce interference from pretreated diatomaceous earth. Step 2b: Dissolve calcium chloride and water-reducing agent in a portion of the water (60-70% of the total water volume), stirring until completely dissolved. 2+ It preferentially forms a solution, which facilitates rapid penetration and activation; Step 2c: First, add the activator solution to the solution obtained in step 2b and stir slowly once, then add the pretreated diatomaceous earth and stir slowly a second time; finally, add the remaining water and stir quickly. In this way, an alkaline / calcium ion environment is first established to activate the activity of slag and red mud; the diatomaceous earth is added later to reduce early water absorption and agglomeration, and is evenly distributed in the already formed hydrated colloidal network; finally, add water to ensure fluidity.
[0039] For example, the stirring speed for the first and second slow stirring is 200~220 r / min and the stirring time is 2~4 min; the stirring speed for the fast stirring is 600~620 r / min and the stirring time is 3~4 min.
[0040] By adjusting the feeding sequence, Ca 2+ and OH - It preferentially acts on the surface of granulated blast furnace slag and red mud particles, quickly initiating the volcanic ash reaction and ion exchange, and fully releasing the activity of the cementing components; diatomaceous earth is added after the slurry has reached a certain viscosity and ion concentration, which can effectively break up its agglomerates with stronger shear force and distribute them evenly in the cementing network, and can also reduce its high water absorption and premature robbing of the free water required for hydration.
[0041] Meanwhile, the later addition of diatomaceous earth allows its porous structure to maintain more complete pore characteristics in the slurry, and the physical interception and surface complexation effects can be fully utilized. While improving strength, it further enhances the long-term curing effect of heavy metals, making it particularly suitable for engineering application scenarios that simultaneously pursue high load-bearing performance and environmental safety.
[0042] Alternatively, step 2 above may include the following steps: Step 2A: Premix half of the total amount of red mud and calcium chloride with some water, let stand for 5-8 minutes, Ca 2+ Pre-displacement of Na on the surface of red mud + This disrupts the passivation film, releasing active Al2O3 and SiO2, allowing the red mud to release its activity earlier and the hydration reaction to be more complete. Step 2B: Add silicate cement and granulated blast furnace slag and dry mix for 2-5 minutes; Step 2C: Add the remaining calcium chloride and water-reducing agent solution to the mixture obtained in Step 2B and stir slowly. Finally, add the pretreated diatomaceous earth and the remaining water and stir quickly.
[0043] For example, the stirring speed of slow stirring is 200~220 r / min and the stirring time is 2~4 min; the stirring speed of fast stirring is 600~620 r / min and the stirring time is 3~4 min.
[0044] Utilizing the Ca in calcium chloride 2+ Pre-treatment of the red mud particles with ion exchange can effectively destroy the passivation film on the surface of the red mud, causing the active Al2O3 and SiO2 that were originally wrapped in the red mud to be exposed and enter the reaction state in advance. This significantly shortens the reaction induction period of the red mud in the cementing system, resulting in an earlier peak of hydration exothermic reaction. At the same time, since the surface properties of the red mud particles are improved in the pre-activation stage, the interfacial bonding between the red mud particles and the subsequently added silicate cement and granulated blast furnace slag is more compact, which is also conducive to the stable growth of the final strength after 28 days.
[0045] In addition, Ca during the red mud pre-activation process 2+ To Na + The displacement effect not only enhances the cementitious activity of red mud itself, but also increases the adsorption sites on the surface of red mud particles (such as Si-O). - Earlier exposure, combined with later synergy with pretreated diatomaceous earth, enables the formation of a denser chemical bond network. This dual activation mechanism helps to immobilize heavy metal ions in the hydrated product lattice, improving the long-term heavy metal leaching stability under acidic conditions, making it particularly suitable for engineering scenarios with high requirements for early strength and durability.
[0046] Example 1: Acid-washed diatomaceous earth modified red mud-based cementitious material S1. Raw material preparation: Bayer process red mud, main chemical composition (mass fraction): Fe2O3, Al2O3, SiO2, Na2O, CaO, particle size d 50 =6.68μm; Ordinary silicate cement P•O42.5R, granulated blast furnace slag: S95 grade, specific surface area 420m² / kg, activity index 98%; Diatomaceous earth: 800 mesh, SiO2 content 88%, original specific surface area 1.81m² / g, pore volume 0.008cm³ / g; Calcium chloride: purity 99%, industrial grade; Polycarboxylate superplasticizer, water reduction rate 28%; ISO standard sand: conforms to GB / T17671-2021 requirements.
[0047] S2. Diatomaceous earth pretreatment: Take 100g of diatomaceous earth, add 250mL of 30% dilute sulfuric acid, solid-liquid ratio 2:5 (g / mL), stir magnetically at 25℃ for 24h, vacuum filter, wash with deionized water until pH=7, dry at 105℃ for 12h, grind, and seal for later use. The specific surface area of the pretreated diatomaceous earth was found to be 2.08m² / g, and the pore volume was 0.013cm³ / g.
[0048] S3. Ingredients and Mixing: Weigh out 50% red mud, 20% cement, 30% blast furnace slag, 10% pickled diatomaceous earth, 2% calcium chloride, and 0.25% water-reducing agent by mass fraction, put them into a planetary mixer, and dry mix at 300 r / min for 2.5 min; add deionized water, control the water-cement ratio at 0.35, slowly mix at 200 r / min for 2 min, and quickly mix at 600 r / min for 4 min to obtain a uniform clean slurry.
[0049] S4. Molding and curing: Pour the slurry into a 40mm×40mm×40mm steel mold, vibrate for 60s to compact, cure at 20℃ and RH=98% for 24 hours to demold, and continue curing for 28 days.
[0050] S5. Performance Tests: 28-day compressive strength 60.3 MPa, flexural strength 10.3 MPa; flowability: 208 mm; in the dynamic leaching test, As leaching concentration was 0.012 μg / L, Cd leaching concentration was 0.008 μg / L, Cr, Ni, and Pb were not detected; leachate pH=11.85.
[0051] Example 2: Acid-washed diatomaceous earth modified red mud-based cementitious material S1. Raw material preparation: Bayer process red mud, main chemical composition (mass fraction): Fe2O3, Al2O3, SiO2, Na2O, CaO, particle size d 50 =6.68μm; Ordinary silicate cement P•O42.5R, granulated blast furnace slag: S95 grade, specific surface area 420m² / kg, activity index 98%; Diatomaceous earth: 800 mesh, SiO2 content 88%, original specific surface area 1.81m² / g, pore volume 0.008cm³ / g; Calcium chloride: purity 99%, industrial grade; Polycarboxylate superplasticizer, water reduction rate 28%; ISO standard sand: conforms to GB / T17671-2021 requirements.
[0052] S2. Diatomaceous earth pretreatment: Take 100g of diatomaceous earth, add 250mL of 30% dilute sulfuric acid, solid-liquid ratio 2:5 (g / mL), stir magnetically at 25℃ for 24h, vacuum filter, wash with deionized water until pH=7, dry at 105℃ for 12h, grind, and seal for later use. The specific surface area of the pretreated diatomaceous earth was found to be 2.08m² / g, and the pore volume was 0.013cm³ / g.
[0053] S3. Ingredients and Mixing: Weigh out 50% red mud, 20% cement, 30% blast furnace slag, 10% pickled diatomaceous earth, 2% calcium chloride, and 0.25% water-reducing agent by mass fraction. Add the red mud, silicate cement, and granulated blast furnace slag to a mixer and dry mix at 300 r / min for 5 min. Dissolve the calcium chloride and water-reducing agent in a portion of the water (60% of the total water volume) and stir until completely dissolved. Add the activator solution to the resulting solution and stir slowly once. Then add the pretreated diatomaceous earth and stir slowly a second time. Finally, add the remaining water and stir rapidly. The stirring speed for the first and second slow stirrings is 200 r / min, and the stirring time is 4 min. The speed for rapid stirring is 600 r / min, and the stirring time is 4 min.
[0054] S4. Molding and curing: Pour the slurry into a 40mm×40mm×40mm steel mold, vibrate for 60s to compact, cure at 20℃ and RH=98% for 24 hours to demold, and continue curing for 28 days.
[0055] S5. Performance Tests: 28-day compressive strength 66.2 MPa, flexural strength 11.1 MPa; flowability: 219 mm; in the dynamic leaching test, As leaching concentration was 0.014 μg / L, Cd leaching concentration was 0.009 μg / L, Cr, Ni, and Pb were not detected; leachate pH=11.88.
[0056] Example 3: Acid-washed diatomaceous earth modified red mud-based cementitious material S1. Raw material preparation: Bayer process red mud, main chemical composition (mass fraction): Fe2O3, Al2O3, SiO2, Na2O, CaO, particle size d 50 =6.68μm; Ordinary silicate cement P•O42.5R, granulated blast furnace slag: S95 grade, specific surface area 420m² / kg, activity index 98%; Diatomaceous earth: 800 mesh, SiO2 content 88%, original specific surface area 1.81m² / g, pore volume 0.008cm³ / g; Calcium chloride: purity 99%, industrial grade; Polycarboxylate superplasticizer, water reduction rate 28%; ISO standard sand: conforms to GB / T17671-2021 requirements.
[0057] S2. Diatomaceous earth pretreatment: Take 100g of diatomaceous earth, add 250mL of 30% dilute sulfuric acid, solid-liquid ratio 2:5 (g / mL), stir magnetically at 25℃ for 24h, vacuum filter, wash with deionized water until pH=7, dry at 105℃ for 12h, grind, and seal for later use. The specific surface area of the pretreated diatomaceous earth was found to be 2.08m² / g, and the pore volume was 0.013cm³ / g.
[0058] S3. Ingredients and Mixing: Weigh out 50% red mud, 20% cement, 30% blast furnace slag, 10% pickled diatomaceous earth, 2% calcium chloride, and 0.25% water-reducing agent by mass fraction. Premix half of the total amount of red mud and calcium chloride with some water and let it stand for 6 minutes. Add silicate cement and granulated blast furnace slag and dry mix for 5 minutes. Add the remaining calcium chloride and water-reducing agent solution to the resulting mixture and stir slowly. Finally, add the pretreated diatomaceous earth and the remaining water and stir quickly. The stirring speed for slow stirring is 200 r / min and the stirring time is 4 minutes; the stirring speed for rapid stirring is 600 r / min and the stirring time is 4 minutes.
[0059] S4. Molding and curing: Pour the slurry into a 40mm×40mm×40mm steel mold, vibrate for 60s to compact, cure at 20℃ and RH=98% for 24 hours to demold, and continue curing for 28 days.
[0060] S5. Performance Tests: 28-day compressive strength 62.7 MPa, flexural strength 10.8 MPa; flowability: 214 mm; in the dynamic leaching test, As leaching concentration was 0.010 μg / L, Cd leaching concentration was 0.006 μg / L, Cr, Ni, and Pb were not detected; leachate pH=11.85.
[0061] Example 4: Calcined diatomaceous earth modified red mud-based cementitious material S1. Raw material preparation: Bayer process red mud, main chemical composition (mass fraction): Fe2O3, Al2O3, SiO2, Na2O, CaO, particle size d 50 =6.68μm; Ordinary silicate cement P•O42.5R, granulated blast furnace slag: S95 grade, specific surface area 420m² / kg, activity index 98%; Diatomaceous earth: 800 mesh, SiO2 content 88%, original specific surface area 1.81m² / g, pore volume 0.008cm³ / g; Calcium chloride: purity 99%, industrial grade; Polycarboxylate superplasticizer, water reduction rate 28%; ISO standard sand: conforms to GB / T17671-2021 requirements.
[0062] S2. Diatomaceous earth pretreatment: Take 100g of 800-mesh diatomaceous earth, put it into a muffle furnace, heat it to 450℃ at 5℃ / min, calcine it at a constant temperature for 180min, cool it and grind it. The specific surface area was found to be 2.53m² / g and the pore volume was 0.019cm³ / g.
[0063] S3. Ingredients and Mixing: Weigh out 45% red mud, 25% cement, 30% blast furnace slag, 10% calcined diatomaceous earth, 2% calcium chloride, and 0.25% water-reducing agent by mass fraction, put them into a planetary mixer, and dry mix at 300 r / min for 2.5 min; add deionized water, control the water-cement ratio at 0.35, slowly mix at 200 r / min for 2 min, and quickly mix at 600 r / min for 4 min to obtain a uniform clean slurry.
[0064] S4. Molding and curing: Pour the slurry into a 40mm×40mm×40mm steel mold, vibrate for 60s to compact, cure at 20℃ and RH=98% for 24 hours to demold, and continue curing for 28 days.
[0065] S5. Performance test: 28-day compressive strength 58.7MPa, flexural strength 9.8MPa; in the dynamic leaching test, Cd adsorption rate 76.2%, As leaching concentration 0.015μg / L, Cr not detected, and leaching solution pH=11.92.
[0066] Example 5: Comparative Test of Different Diatomite Contents S1. Raw material preparation: Bayer process red mud, main chemical composition (mass fraction): Fe2O3, Al2O3, SiO2, Na2O, CaO, particle size d 50 =6.68μm; Ordinary silicate cement P•O42.5R, granulated blast furnace slag: S95 grade, specific surface area 420m² / kg, activity index 98%; Diatomaceous earth: 800 mesh, SiO2 content 88%, original specific surface area 1.81m² / g, pore volume 0.008cm³ / g; Calcium chloride: purity 99%, industrial grade; Polycarboxylate superplasticizer, water reduction rate 28%; ISO standard sand: conforms to GB / T17671-2021 requirements.
[0067] S2. Diatomaceous earth pretreatment: Take 100g of diatomaceous earth, add 500mL of 30% dilute sulfuric acid, solid-liquid ratio 1:5 (g / mL), stir magnetically at 20℃ for 36h, vacuum filter, wash with deionized water until pH=7, dry at 100℃ for 18h, grind, and seal for later use. The specific surface area of the pretreated diatomaceous earth was found to be 2.10m² / g, and the pore volume was 0.015cm³ / g.
[0068] S3. Ingredients and Mixing: Weigh out 50% red mud, 20% cement, 30% blast furnace slag, pickled diatomaceous earth, 2% calcium chloride, and 0.25% water-reducing agent by mass fraction. The amount of pickled diatomaceous earth added is 5% (Comparative Example 5-1), 10% (Example 5-1), 15% (Example 5-2), and 20% (Comparative Example 5-2). Put it into a planetary mixer and dry mix at 300 r / min for 2.5 min. Add deionized water, control the water-cement ratio at 0.35, and slowly mix at 220 r / min for 4 min and then quickly mix at 620 r / min for 3 min to obtain a uniform clean slurry.
[0069] S4. Molding and curing: Pour the slurry into a 40mm×40mm×40mm steel mold, vibrate for 60s to compact, cure at 22℃ and RH=97% for 36 hours to demold, and continue curing for 28 days.
[0070] The properties of the prepared neat pulp samples were tested after 28 days of curing. The results are shown in the table below:
[0071] The best overall performance is achieved when the diatomaceous earth content is 10%. When the content is less than 10%, there are insufficient adsorption sites, and the improvement in heavy metal curing effect and mechanical properties is limited. When the content is greater than 10%, the high water absorption of diatomaceous earth leads to a decrease in the effective water-cement ratio of the slurry, an increase in the internal porosity of the matrix, and a downward trend in strength. However, the fluidity meets the engineering requirements (≥197mm).
[0072] Furthermore, at 20%, the compressive strength dropped to 52.1 MPa, a decrease of 13.6%. The main reasons are: the high specific surface area and strong water absorption of diatomaceous earth lead to a decrease in the effective water-cement ratio, resulting in poor workability of the slurry and an increase in internal capillary pores; excessive inert or low-activity components dilute the effective reactant ratio of the cementitious system (cement + slag) and weaken the network structure of hydration products.
[0073] Example 6: Mortar Performance Verification S1. Preparation process: According to the proportion of Example 1, add ISO standard sand, control the mass ratio of cementitious material (red mud + cement + blast furnace slag + diatomite) to standard sand to 1:3, water-cement ratio to 0.35, add water and stir slowly for 2 minutes + stir quickly for 2 minutes, pour into a 40mm×40mm×160mm steel mold, vibrate to compact and then cure for 28 days. S2. Performance test results: 28-day compressive strength 59.7 MPa, flexural strength 9.7 MPa; flowability 205 mm, meeting pumping requirements; impermeability test (GB / T50082-2009) shows permeability coefficient ≤1×10⁻⁶. -7cm / s; Cr leaching concentration 17.6 μg / L, leaching inhibition rate 49.9%, which meets the requirements of GB / T30760–2024 "Soil Environmental Quality Standard for Construction Land Soil Pollution Risk Control".
[0074] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for the resource utilization of coal-based solid waste, characterized in that, Includes the following steps: Step 1: Pre-treat the diatomaceous earth to obtain pre-treated diatomaceous earth; Step 2: Weigh the raw materials and mix them evenly to obtain a mixture; Step 3: Add water to the mixture and stir. The water-to-binder ratio is 0.35~0.5 to form a uniform slurry. Step 4: Pour the uniform slurry into the mold and vibrate it to compact it, so as to obtain the molded diatomaceous earth modified red mud-based cementitious material; The raw materials include a dry mixture and an activator. The dry mixture comprises, by mass fraction, 40-50 parts red mud, 20-40 parts silicate cement, and 20-30 parts granulated blast furnace slag. The activator comprises, by percentage of the total mass of the dry mixture, 10-15 parts pretreated diatomaceous earth, 1-3 parts calcium chloride, and 0.2-0.3 parts water-reducing agent.
2. The method for resource utilization of coal-based solid waste according to claim 1, characterized in that, The pretreatment in step 1 is acid washing pretreatment.
3. The method for resource utilization of coal-based solid waste according to claim 2, characterized in that, In step 1, the pickling pretreatment includes the following steps: Diatomaceous earth raw material is mixed with 30% dilute sulfuric acid at a solid-liquid ratio of 1~2:5 g / mL, stirred at 20~30℃ for 24~36h, vacuum filtered, washed with deionized water until the pH of the filtrate is 7, and dried at 100~105℃ to constant weight to obtain pretreated diatomaceous earth.
4. The method for resource utilization of coal-based solid waste according to claim 1, characterized in that, The pretreatment in step 1 is a calcination pretreatment.
5. The method for resource utilization of coal-based solid waste according to claim 4, characterized in that, In step 1, the calcination pretreatment includes the following steps: The diatomaceous earth raw material is heated to 450-480℃ at a heating rate of 5-8℃ / min, calcined at a constant temperature for 150-180min, and then naturally cooled to obtain pretreated diatomaceous earth.
6. The method for resource utilization of coal-based solid waste according to any one of claims 1 to 5, characterized in that, Following step 5, the following steps are also included: Curing of the formed diatomaceous earth modified red mud-based cementitious material.
7. The method for resource utilization of coal-based solid waste according to claim 6, characterized in that, The maintenance in step 1 includes the following steps: After the molded diatomaceous earth-modified red mud-based cementitious material is cured at a temperature of 18~22℃ and a relative humidity of ≥95% for 24~36 hours, it is demolded and then cured for a longer period.
8. The method for resource utilization of coal-based solid waste according to any one of claims 1 to 5, characterized in that, Step 2 includes the following steps: Step 2a: Dry mix red mud, silicate cement, and granulated blast furnace slag at 300~350 r / min for 2~5 min; Step 2b: Dissolve calcium chloride and water-reducing agent in a portion of water beforehand, and stir until completely dissolved; Step 2c: First, add the activator solution to the solution obtained in step 2b and stir slowly once, then add the pretreated diatomaceous earth and stir slowly a second time; finally, add the remaining water and stir quickly.
9. The method for resource utilization of coal-based solid waste according to claim 8, characterized in that, The stirring speed for the first and second slow stirring is 200~220 r / min, and the stirring time is 2~4 min.
10. The method for resource utilization of coal-based solid waste according to claim 8, characterized in that, The speed of the rapid stirring is 600~620 r / min, and the stirring time is 3~4 min.